Factors affecting return on deposit (ROD) of sharia banks in Indonesia - Wahyudi, Sugeng; Nofendi, Deki; Robiyanto, Robiyanto; Hersugondo, Hersugondo (Business: Theory and Practice, 2018)
This study examines the effect of Capital Adequacy Ratio (CAR), Financing to Deposit Ratio (FDR), board of directors’ size (BOARD), sharia supervisory board (DPS), bank size (SIZE), and interest rate (INT) and sharia bank ownership status (DFOR) to Return on Deposit (ROD). The sample used in this research is 11 sharia banks operating in Indonesia. By using multiple regression analysis technique, it was found that CAR and SIZE have a significant negative effect on ROD) of sharia banks in Indonesia. While the FDR, BOARD and INT have a significant positive effect on ROD of sharia banks in Indonesia. Meanwhile, DPS and DFOR have no significant effect on ROD of sharia bank in Indonesia.